Design 8-bit risc processor base on x86 architecture using VHDL / Musnazril Mustaq Khan - Mustaq Khan, Musnazril (2004)
This paper presents the process of building a basic x86 RISC processor using VHDL. The RISC conceptual design had been taken out from the complex CISC X86-Architecture. The development process is performed using VHDL programming language and optimized using Xilinx schematic editor. The modules designed are the Arithmetic Logic Unit, Control Unit and Register Set. The tests performed are based on a special test program, which is build inside the processor Read Only Memory.